Determination of dynamical models for adaptive control systems - Paul, R. J. A. (College of Aeronautics, 1962)
A method is described for the synthesis of a dynamical model of a linear system based on the use of orthonormal functions. It is shown that if the nominal values of all poles of a system are known, and if only one pole changes from its nominal value, then this change may be detected. It is also demonstrated that the numerator terms of the transmission transfer function of the system may be found provided the denominator is known. Active networks are described, for the simulation of the relevant orthonormal functions.